Embryonic amygdalar transplants in adult rats with motor cortex lesions: A molecular and electrophysiological analysis (2011)
Transplants of embryonic nervous tissue ameliorate motor deficits induced by motor cortex lesions in adult animals. Restoration of lost brain functions has been recently shown in grafts of homotopic cortical origin, to be associated with a functional integration of the transplant after development of reciprocal host-graft connections. Nevertheless little is known about physiological properties or gene expression profiles of cortical implants with functional restorative capacity but no cortical origin. In this study, we show molecular and electrophysiological evidence supporting the functional development and integration of heterotopic transplants of embryonic amygdalar tissue placed into pre-lesioned motor cortex of adult rats. Grafts were analyzed 3 months post-transplantation.